2017
DOI: 10.1093/ije/dyx075
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural, not biological, factors drive the HCV epidemic among HIV-positive MSM: HCV and HIV modelling analysis including HCV treatment-as-prevention impact

Abstract: Sexual behaviour patterns likely drive observed HCV infection patterns among HIV-positive MSM. Changes in these patterns could disseminate HCV amongst HIV-negative MSM, limiting the impact of targeting HCV treatment to HIV-diagnosed MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Although we found an association between virus phylogeny and the traits of HIV‐seropositivity and age within cluster 4, this was not observed for the other three clusters. The overall lack of structure for HIV status within the clusters supports the notion that behavioural factors may be more critical than biological factors for driving the HCV epidemic amongst MSM, as modelling studies have predicted . For HIV‐negative individuals, it seems implausible that PrEP itself should increase HCV susceptibility.…”
Section: Discussionmentioning
confidence: 61%
“…Although we found an association between virus phylogeny and the traits of HIV‐seropositivity and age within cluster 4, this was not observed for the other three clusters. The overall lack of structure for HIV status within the clusters supports the notion that behavioural factors may be more critical than biological factors for driving the HCV epidemic amongst MSM, as modelling studies have predicted . For HIV‐negative individuals, it seems implausible that PrEP itself should increase HCV susceptibility.…”
Section: Discussionmentioning
confidence: 61%
“…Mother-to-child transmission of HCV results in some individuals entering the model chronically infected. This occurs at a rate dependent on the number of HCV-infected women of childbearing age (modelled as [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and their HIV co-infection prevalence 14 . Once infected, individuals either spontaneously clear their infection, and become susceptible again, or develop lifelong chronic infection.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Similarly, we were unable to include HCV epidemics among MSM within our model due to a scarcity of information around prevalences globally. However, studies indicate that although transmission among MSM is much higher than among heterosexual couples, incidence and prevalence is still low compared with PWID 31 and likely contributes little to the epidemic in comparison 32 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In fact, an increasing incidence of sexual HCV transmission has been observed in large European, North American and Asiatic cities, although at a lower level than in HIV‐positive MSM . Therefore, it has been suggested that all MSM at high risk (especially those receiving pre‐exposure prophylaxis for HIV, or practicing slamming) should be screened for HCV infection and other STIs, and should be the focus of prevention efforts . Commercial sex workers are prioritized for HCV screening by WHO, as they are vulnerable groups at high risk for STIs with poor access to the healthcare system .…”
Section: Discussionmentioning
confidence: 99%